Integrasi strategi digitalisasi, manajemen risiko, dan inovasi produk dalam meningkatkan daya saing perbankan syariah di indonesia - Fadhila, Adzkiya Nayla (Maliki Interdisciplinary Journal, 2025)
Digital transformation is a crucial strategy for Islamic banks to survive and thrive amidst various disruptions from the financial technology sector. Digitalization, risk management, and product development are three key foundations that mutually support the competitiveness of Islamic banks in Indonesia. This study aims to build an efficient, secure, and sustainable Islamic banking system. The results show that digitalization can improve efficiency and customer satisfaction, risk management strengthens stability and public trust, while product innovation helps expand the market and increase the relevance of Islamic services. By combining these three strategies, Islamic banks can generate sustainable competitive advantages in accordance with the values ​​of maqāṣid al-sharī‘ah, particularly in achieving the welfare of the community and maintaining trust in financial management. This study also emphasizes the importance of Sharia-compliant digital strategy planning, developing human resource capabilities to address digital risks, and collaborating with fintech companies to encourage more inclusive Islamic product innovation.